Nomophobia in Adolescents: A Comprehensive Literature Review Based on Albert Bandura's Social Cognitive Theory - Sarah Juwita; Diah Karmiyati (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
This study examines the phenomenon of nomophobia (no mobile phone phobia) in Indonesian adolescents, linking it with Albert Bandura's social cognitive theory of personality. Nomophobia is defined as anxiety or discomfort caused by the inability to access a smartphone. Indonesia has a high prevalence of internet users, particularly among adolescents, which potentially increases the risk of nomophobia. This research employs a comprehensive literature review method to explore the relationship between internal factors, such as self-efficacy and self-regulation as explained in Bandura's theory, and the level of nomophobia in adolescents. Data were collected from various academic sources and analysed using both qualitative and quantitative approaches. The results indicate that the level of nomophobia among Indonesian adolescents is significant, negatively impacting their psychological, social, and academic aspects. Bandura's social cognitive theory explains how the interaction between environment, behavior, and personal factors such as self-efficacy and self-regulation contributes to the level of nomophobia. This understanding is crucial for developing effective intervention strategies and policies to reduce the negative impact of nomophobia and enhance adolescent well-being in the digital era.